Trends of Gender Gaps in Nepal: A Statistical Analysis - Gautam, Susmita (Nepalese Journal of Development and Rural Studies, 2023)
This paper applied two panel data on GII (1996 to 2022),and EFI (1996-2022) to understand the trends of gender gap in Nepal. Recently, UNDP (2023b) has developedGSNIbased on data from wave 6 (2010-2014) and wave 7 (2017-2022) of WVS (2023). However, index is not available for Nepal. In this context, this article examined dimensions of WVS by defining gender gap in four thematic areas such as secondary education, representation in parliament, participation in labor force, and life expectancy, suggesting they are associated with ODA and some economic freedom indices.